Determination of trichlorfon in samples of spicy vegetables using a molecularly imprinted solid-phase extraction technique. Issue 6 (11th February 2015) - Xue, Min; Shen, Jingyao; Wang, Dan; Yin, Lei; Zhuang, Xiaolei; Meng, Zihui
Abstract : Trichlorfon is a widely used organophosphate insecticide that has adverse effects on human health. Abstract : Trichlorfon is a widely used organophosphate insecticide that has adverse effects on human health. The complexity of the matrix encountered in vegetables, especially spicy vegetables, makes the determination of trace amounts of trichlorfon difficult. We used a molecularly imprinted solid-phase extraction technique to concentrate the trace amounts of trichlorfon present in samples of ginger, bunching onion ( Allium fistulosum ), onion, garlic and chili. Recoveries of 80.2–89.3% (RSD 2.5–3.5%, n = 5) and a limit of detection of 0.05 μg mL −1 were obtained for trichlorfon by using a solid-phase extraction cartridge filled with 30 mg of molecularly imprinted polymers coupled with detection by high-performance liquid chromatography. This method gave better results than commercial C18 sorbents with regard to the efficiency of removal of any matrix effects.